A self-colored waterborne polyurethane film with natural curcumin as a chain extender and excellent UV-Absorbing properties. (17th January 2022) - Zhang, Tao; Deng, Yajun; Zhang, Wenshuo; Wang, Guannan; Zhong, Yuye; Su, Cheng; Li, Houbin
Abstract: To follow the sustainable tendency, natural resources have been attractive to fabricate the functional materials in various applications. In this present study, curcumin, a natural pigment, was used as a chain extender to synthesize a series of environmentally friendly waterborne polyurethane to prepare self-colored waterborne polyurethane films with excellent ultraviolet (UV) absorption properties. The effect of curcumin content on the performance of waterborne polyurethane film was investigated from the aspects of transparency, thermal stability and mechanical properties. The chemical structure of waterborne polyurethane was systematically characterized by Fourier transform infrared (FT-IR), gel permeation chromatography (GPC) and 1 H nuclear magnetic resonance ( 1 H NMR) spectrums. The transmittance of the WPU-0 without curcumin as control sample was 89.27%, in which the films WPU-1, WPU-2 and WPU-3 respectively decreased the transmittance to 87.69%, 84.38% and 76.89%, and absorbs nearly 100% in UVA (315–400 nm) and UVB (280–315 nm) radiations with increasing of the curcumin content. The thermogravimetric analysis (TGA-DTG) curves showed that the introduction of curcumin could effectively improve the thermal stability of different films. Besides, four waterborne polyurethane films were carried out the tensile stress-strain measurement to investigate the mechanical properties. When adding 6% curcumin chain extender, the stress of WPU-1 film increased to 28.73 MPa relative to the control sample WPU-0 which of the value was only 12.45 MPa. Beyond expectation, while adding 12% and 18% curcumin content, the stress of WPU-2 and WPU-3 films gradually decreased to 20.18 MPa and 11.48 MPa, respectively. In addition, as increasing 18% proportion of curcumin, the elongation at break gradually decreased, specifically, the value at 555% of the WPU-0 sharply reduced to 233% of the WPU-3, indicating that the brittleness of the curcumin-based waterborne polyurethane was increased. The results showed that the naturally green curcumin was incorporated into the waterborne polyurethane structure, and an environmentally-friendly waterborne polyurethane film with good mechanical properties and transparency could been obtained with its own color. Graphical abstract: Synopsis: A self-colored waterborne polyurethane film with natural curcumin as a chain extender and excellent UV-Absorbing Properties. Image 1 Highlights: Synthesized of an anionic waterborne polyurethane using curcumin as a chain extender. Natural curcumin was used as a chain extender to synthesize waterborne polyurethane with self-coloring. Waterborne polyurethane with curcumin as chain extender had excellent UV absorption properties. The mechanical properties of waterborne polyurethane with curcumin as a chain extender had been improved.